The Son Of Neptune (Heroes of Olympus, 2, 1, 2013)
Demigod Percy Jackson, still with no memory, and his new friends from Camp Jupiter, Hazel and Frank, go on a quest to free Death, but their bigger task is to unite the Greek and Roman camps so that the Prophecy of Seven can be fulfilled.

The key to everything (Candlewick on BrillianceAudio, ,, 2018)
Returning from camp, eleven-year-old Tash is dismayed to find that her elderly next-door neighbor has disappeared and is compelled to use the key that may possess magic.

Holes (Thorndike Press large print literacy bridge, ,, 1998)
As further evidence of his family's bad fortune which they attribute to a curse on a distant relative, Stanley Yelnate is sent to a hellish correctional camp in the Texas desert where he finds his first real friend, a treasure, and a new sense of himself.

The House of Hades (Heroes of Olympus, 4, 1, 2013)
At the conclusion of The Mark of Athena, Annabeth and Percy tumble into a pit leading straight to the Underworld. The other five demigods have to put aside their grief and follow Percy's instructions to find the mortal side of the Doors of Death. If they can fight their way through Gaea's forces, and Percy and Annabeth can survive the House of Hades, then the Seven will be able to seal the Doors on both sides and prevent the giants from raising Gaea.

Amelia Bedelia goes camping (Amelia Bedelia series, 10, 1, 1986)
As always, Amelia Bedelia follows exactly the instructions given to her on a camping trip, including pitching a tent and rowing boats.

The hidden oracle (Trials of Apollo, 1, 1, 2017)
"After angering his father Zeus, the god Apollo is cast down from Olympus. He must learn to survive in the modern world until he can somehow find a way to regain Zeus's favor"-- How do you punish an immortal? By making him human. After angering his father Zeus, the god Apollo is cast down from Olympus. Weak and disorientated, he lands in New York City as a regular teenage boy. Now, without his godly powers, the four-thousand-year-old deity must learn to survive in the modern world until he can somehow find a way to regain Zeus's favor. But Apollo has many enemies -- gods, monsters, and mortals who would love to see the former Olympian permanently destroyed. Apollo needs help, and he can think of only one place to go ... an enclave of modern demigods known as Camp Half-Blood.

Treasure Island (A Signet classic CE1610, ,, 1975)
"Young Jim Hawkins and his friends set sail for Treasure Island, hoping to find the buried loot of Captin Flint, fiercest of all the pirates. But, unknown to them, the crew of their own ship is made up of Flint's former crew, led by the evil one-legged pirate Long John Silver. Once on the island Jim and his friends must find the buried treasure and escape before the pirates capture them. Robert Louis Stevenson's timeless tale of greed and gold remains the most exciting adventure story ever written."--P. [4] of cover.
Old buccaneer , Sea cook , My shore adventure , Stockade , My sea adventure , Captain Silver , Questions, questions, questions / Arthur Pober , About the author, about the illustrator.

The devil's arithmetic (Recorded Books, Inc., Penguin, Viking Kestrel, Scholastic, Puffin Books, 1996)
Hannah resents stories of her Jewish heritage and of the past until, when opening the door during a Passover Seder, she finds herself in Poland during World War II where she experiences the horrors of a concentration camp, and learns why she-- and we--need to remember the past.

Little house on the prairie (Little house (Laura Ingalls Wilder), 2, 1, 1953)
Pa Ingalls decides to sell the old house, and the family sets out for Indian Country! They travel from Wisconson to Kansas and there, finally, Pa builds their little house on the prairie. Sometimes farm life is difficult, even dangerous, but Laura and the family are kept busy and are happy with the promise of their new life on the prairie.
Going west , Crossing the creek , Camp on the high prairie , Prairie day , House on the prairie , Moving in , Wolf-pack , Two stout doors , Fire on the hearth , Roof and a floor , Indians in the house , Fresh water to drink , Texas longhorns , Indian camp , Fever "n' ague , Fire in the chimney , Pa goes to town , Tall Indian , Mr. Edwards meets Santa Claus , Scream in the night , Indian jamboree , Prairie fire , Indian war-cry , Indians ride away , Soldiers , Going out.

The lightning thief (Percy Jackson & the Olympians, 1, 1, 2009)
"Percy Jackson is about to be kicked out of boarding school...again. And that's the least of his troubles. Lately, mythological monsters and the gods of Mount Olympus seem to be walking straight out of the pages of Percy's Greek mythology textbook and into his life. And worse, he's angered a few of them. Zeus's master lightning bolt has been stolen, and Percy is the prime suspect." -- from front jacket flap.
I accidentally vaporize my pre-algebra teacher , Three old ladies knit the socks of death , Grover unexpectedly loses his pants , My mother teaches me bullfighting , I play pinochle with a horse , I become supreme lord of the bathroom , My dinner goes up in smoke , We capture a flag , I am offered a quest , I ruin a perfectly good bus , We visit the Garden Gnome Emporium , We get advice from a poodle , I plunge to my death , I become a known fugitive , God buys us cheeseburgers , We take a zebra to Vegas , We shop for water beds , Annabeth does obedience school , We find out the truth, sort of , I battle my jerk relative , I settle my tab , Prophecy comes true.

Small Steps (Holes, ,, 2006)
Three years after being released from Camp Green Lake, Armpit is trying hard to keep his life on track, but when his old pal X-Ray shows up with a tempting plan to make some easy money scalping concert tickets, Armpit reluctantly goes along.

Brian's hunt (Brian's saga, 5, 1, 2007)
Two years after he survived a plane crash in the Canadian wilderness, a sixteen-year-old returns to the wild where he feels he belongs. In a temporary camp on the way to visit his friends, Brian Robeson finds a dog, wounded and whimpering. The dog is badly hurt, and as Brian cares for it, he worries about his friends. His instincts tell him to head north, quickly. With his new companion at his side, and with a terrible, growing sense of unease, he sets out to learn what happened.

The battle of the Labyrinth (Percy Jackson & the Olympians, 4, 1, 2009)
When demonic cheerleaders invade his high school, Percy Jackson hurries to Camp Half Blood, from whence he and his demigod friends set out on a quest through the Labyrinth, while the war between the Olympians and the evil Titan lord Kronos draws near.

The adventures of Huckleberry Finn (Classic collection), ,, 2011)
Called "the veriest trash" by a member of the Concord, Massachusetts Library Board that banned the novel when it was first published, Huckleberry Finn has come to be viewed, as H.L. Mencken put it, as "one of the great masterpieces of the world." Ernest Hemingway wrote that "All modern American literature comes from one book by Mark Twain called Huckleberry Finn....There was nothing before. There has been nothing as good since." A daringly ironic attack on racism American-style, Twain's story of what he once called a "sound heart" triumphing over a "deformed conscience" is poignant, powerful, and fresh. It is no wonder that this extraordinary book continues to captivate readers around the world. This handsome Oxford World's Classic edition uses the reliable 1885 text and includes in-depth, up-to-date editorial apparatus
Discover Moses and the bulrushers , Our gang's dark oath , We ambuscade the A-rabs , Hair-ball oracle , Pap starts in on a new life , Pap struggles with the Death Angel , I fool Pap and get away , I spare Miss Watson's Jim , House of death floats by , What comes of handlin snake-skin? , They're after us! , "Better let blame well alone" , Honest loot from the "Walter Scott" , Was Solomon wise? , Fooling poor old Jim , Rattlesnake-skin does its work , Grangerfords take me in , Why Harney rode away for his hat , Duke and the Dauphin come aboard , What royalty did to Parkville , Arkansaw difficulty , Why the lynching bee failed , Orneriness of kings , King turns parson , All full of tears and flapdoodle , I steal the king's plunder , Dead Peter has his gold , Overreaching don't pay , I light out in the storm , Gold saves the thieves , You can't pray a lie , I have a new name , Pitiful ending of royalty , We cheer up Jim , Dark, deep-laid plans , Trying to help Jim , Jim gets his witch pie , "Here a captive heart busted" , Tom writes nonnamous letters , Mixed-up and splendid rescue , "Must 'a' been sperits" , Why the didn't hang Jim , Last. Nothing more to write.

Little women (Little Women series, 1, 1, 2012)
For generations, children around the world have come of age with Louisa May Alcott's March girls: hardworking eldest sister Meg, headstrong, impulsive Jo, timid Beth, and precocious Amy. With their father away at war, and their loving mother Marmee working to support the family, the four sisters have to rely on one another for support as they endure the hardships of wartime and poverty. We witness the sisters growing up and figuring out what role each wants to play in the world, and, along the way, join them on countless unforgettable adventures. Readers young and old will fall in love with this beloved classic, at once a lively portrait of nineteenth-century family life and a feminist novel about young women defying society's expectations.
Four sisters , A merry Christmas , The Laurence boy , Being neighborly , Jo and her temper , Meg tries to be fashionable , Summer and dreams , Secrets , A telegram , Dark days , Serious conversations , Aunt March settles the question , The first wedding , Endeavors , Domestic experiences , Calls , Jo's friend , Heartache , Beth's secret , Lazy Laurence , The Valley of the Shadow , Learning to forget , All alone , Under the umbrella.

Warriors in winter (Magic tree house. Original series, 31, 1, 2019)
"The magic tree house whisks Jack and Annie back in time to meet famed Roman emperor Marcus Aurelius!"--

The adventures of Tom Sawyer (The Mark Twain in Person Audio Library, ,, 2012)
"Mark Twain's classic The Adventures of Tom Sawyer has been enjoyed by generations of readers across the world since its publication in 1876. With its humorous glimpses into life in nineteenth-century, small-town America, this novel has provided unique social commentary that continues to be discussed in classrooms today. Tom Sawyer, a mischievous boy growing up in the fictional town of St. Petersburg, Missouri, is constantly getting in and out of trouble with his friend Huckleberry Finn. Based on Twain's own childhood, this novel not only gives profound insights into American life but also shows how children can develop moral codes based on friendship, loyalty, and respect"--
15 copies of the audiobook.

Sunny Song will never be famous (Sourcebooks Inc, Dreamscape Media LLC, Dreamscape Media, Sourcebooks Fire, 2022)
"A social media influencer is shipped off to a digital detox summer camp in this funny coming-of-age story"--

Between shades of gray (Thorndike Press large print The literacy bridge, ,, 2012)
In 1941, fifteen-year-old Lina, her mother, and brother are pulled from their Lithuanian home by Soviet guards and sent to Siberia, where her father is sentenced to death in a prison camp while she fights for her life, vowing to honor her family and the thousands like hers by burying her story in a jar on Lithuanian soil. Based on the author's family, includes a historical note.

Here in the real world (Balzer + Bray, HarperCollins, Balzer + Bray, an imprint of HarperCollins Publishers, Harper Audio, HarperCollins Publishers, 2020)
"Ware can’t wait to spend summer 'off in his own world'—dreaming of knights in the Middle Ages and generally being left alone. But then his parents sign him up for dreaded Rec camp, where he must endure Meaningful Social Interaction and whatever activities so-called 'normal' kids do. On his first day Ware meets Jolene, a tough, secretive girl planting a garden in the rubble of an abandoned church next to the camp. Soon he starts skipping Rec, creating a castle-like space of his own in the church lot. Jolene scoffs, calling him a dreamer—he doesn’t live in the “real world” like she does. As different as Ware and Jolene are, though, they have one thing in common: for them, the lot is a refuge. But when their sanctuary is threatened, Ware looks to the knights’ Code of Chivalry: Thou shalt do battle against unfairness wherever faced with it. Thou shalt be always the champion of the Right and Good—and vows to save the lot. But what does a hero look like in real life? And what can two misfit kids do?" --book jacket